High-resolution records of sulfur and insoluble particle concentrations from the Summit2023 ice core in Greenland between 1666 and 1670 CE and inferred volcanic contributions - Michael Sigl; Joseph R McConnell; Nathan J Chellman; Imogen Gabriel (PANGAEA, 2025)
We report high resolution (2.5 cm depth) sulfur concentrations from the Summit2023 ice core in Greenland analyzed using inductively coupled plasma mass spectrometry (ICPMS) and mass concentrations of insoluble particles (5-10um size) using an inline Abakus® laser particle counter at the Desert Research Institute. Details about the analytical procedures are provided in the references. We subtract represenative background values from the total sulfur concentrations to derive volcanic sulfate concentrations (ng g-1). These records are used alongside ice-core crypto-tephra to characterize volcanic eruption sources and to disentangle individual volcanic sulfur depositions on the polar ice sheet arising from temporal clusters of volcanic eruptions in the 1660s CE.
In: Sigl, M et al. (2025): High time resolution records of sulfur and insoluble particle concentrations from five ice cores from Greenland and one from Antarctica between 1530 and 1710 CE and inferred volcanic contributions [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.974177